Middle Income Trap: Mengapa Indonesia Sulit Menembus Major Power Global? - Muhammad Muslim (Universitas Diponegoro, 2025)
The projection of Indonesia as the country with the fourth-largest economic power in 2045 has become one of the most widely discussed discourses, especially in the second term of President Joko Widodo's administration. The main argument is that Indonesia will receive a demographic dividend. Regarding economic material capacity, Indonesia's contribution to the global economy based on GDP, for example, is still far behind that of major powers. Indonesia's economic development exposure will not increase exponentially if it only relies on GDP growth. Indonesia's GDP in 2023 is equivalent to Italy's GDP in 2002. This means that Indonesia must wait a long time, or at least 21 years, until 2045 to become a new world economic power. This article tries to offer a conceptual idea that Indonesia must take first to realize its ambition as a new world power. Instead of relying only on material capacity, Indonesia needs to define its status in international relations. If not, then Indonesia will increasingly fall into the middle power trap, which hinders its steps to becoming a new major relevant power.Keywords: Indonesia, GDP, new major relevance power, middle power trap